2013
DOI: 10.14366/usg.13017
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of acoustic radiation force impulse elastography in the differential diagnosis of benign and malignant solid pancreatic lesions

Abstract: Purpose:The aim of this study was to evaluate the tissue stiffness of solid pancreatic lesions by using acoustic radiation force impulse (ARFI) elastography to differentiate benign from malignant pancreatic lesions.Methods:ARFI elastography was performed in 26 patients who had 27 focal solid pancreatic lesions, including 8 benign lesions (mass-forming pancreatitis, 5; autoimmune pancreatitis, 3) and 19 malignant lesions (pancreatic adenocarcinoma, 16; metastasis from colorectal cancer, 2; malignant neuroendocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 27 publications
1
43
0
2
Order By: Relevance
“…A study reported the usefulness of VTQ for differential diagnosis between malignant and benign pancreatic tumors [41] , and another reported the usefulness of VTQ for diagnosis of acute pancreatitis [42] . There is also a study reporting the possibility of discriminating serous cyst fluid from mucinous one [43] .…”
Section: Us-elastography -Shear Wave Elastograhymentioning
confidence: 99%
“…A study reported the usefulness of VTQ for differential diagnosis between malignant and benign pancreatic tumors [41] , and another reported the usefulness of VTQ for diagnosis of acute pancreatitis [42] . There is also a study reporting the possibility of discriminating serous cyst fluid from mucinous one [43] .…”
Section: Us-elastography -Shear Wave Elastograhymentioning
confidence: 99%
“…Currently, ARFI and SWEI methods have been implemented on Siemens Acuson ultrasound scanner as Virtual Touch Tissue Imaging and Virtual Touch Tissue Quantification, respectively [8]. Both techniques have been demonstrated useful for diagnosing pancreatic tumor, pancreatic fibrosis, and pancreatitis [14]–[17]. Although non-invasive, making these two methods appropriate for screening asymptomatic patients, their successful application in the abdominal organs faces a unique challenge: they are sensitive to physiologic motion [14].…”
Section: Introductionmentioning
confidence: 99%
“…The lesion detection rate and diagnostic rate could be improved to over 90% by the combined use of B-mode and elastographic images, compared to using b-mode images alone (Uchida et al, 2009;Park et al, 2014). This technique has been reported to be useful in characterizing and differentiating normal pancreas, chronic pancreatitis and acute pancreatitis.…”
Section: Primary Applications Of Elastographymentioning
confidence: 99%
“…Higher ARFI values in acute pancreatitis are due to increased fluid content in the inflamed organ making the tissue hard (Mateen et al, 2012). Another study (Janssen et al, 2007) concluded that chronic pancreatitis and hard tumors cannot be distinguished by elastography, probably because of their similar fibrous structure and calcification, leading to high ARFI values (Janssen et al, 2007;Park et al, 2014).…”
Section: Primary Applications Of Elastographymentioning
confidence: 99%